Effects of application of water and nitrogen on nutrient use from corn and sorghums by pigs - Richert, B.T.; Bramel-Cox, P.J.; Witt, Merle D.; Healy, B.J.; Hancock, Joe D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
An experiment was conducted to determine the effects of growing conditions on nutrient yield and quality of corn and sorghum. Main effect treatments were: corn (C), bronze pericarp heterozygous-yellow endosperm sorghum (BS), and yellow pericarp homozygous-yellow endosperm sorghum (YS); optimal irrigation (I) and minimal irrigation (MI); 100 lb/acre of N fertilization (F) and no N fertilization (NF), in a 3 × 2 × 2 factorial arrangement. Grains were grown in 1988 (Year 1, with little rainfall) and 1989 (Year 2, with above average rainfall) in the semi-arid environment at Garden City, KS. In Year 1, sorghums yielded 15% more grain than C, and YS yielded 1.2% more grain than BS. Irrigation increased yield by 90%, and N application increased yield by 7%. In year 2, C yielded 11% more grain than the sorghums. In the pig metabolism study, C had greater nitrogen digestibility (ND) than sorghums in both years, greater biological value (BV) and nitrogen retention in Year 2, but lower BV in Year 1. Yellow sorghum had greater ND than BS in Year 1. Corn had increased cost per unit of utilizable nitrogen (CUN) and utilizable energy (CUE) and reduced utilizable nitrogen per inch of available water (UNW) and utilizable energy per inch of available water (UEW) for both years compared to BS and YS. In conclusion, optimally irrigated grains had higher nutritional value than minimally irrigated grains, and growing the grains under varying agronomic conditions did affect their nutritional quality.
Keywords: Swine; Corn; Sorghum; Irrigation; Fertilization; Digestibility